Merdeka Belajar–Kampus Merdeka (MBKM) Policy Implementation and Learning Quality: The Role of Religious Moderation in Islamic Higher Education - Wan Jamaluddin; Yuberti Yuberti; Nanang Supriadi; Bambang Budi Wiranto; Ardian Asyhari (Smart Society, 2026)
This study examines the impact of the Merdeka Belajar–Kampus Merdeka (MBKM) policy implementation on learning quality in Islamic Higher Education Institutions, with particular attention to the integration of religious moderation as a value-based educational framework. Employing an explanatory sequential mixed-methods design, the study combines Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis of survey data from 400 students across diverse PTKIs in Indonesia with qualitative insights from 15 key informants, including lecturers and institutional leaders. The results indicate that MBKM implementation has a significant positive effect on learning quality (β=0.090, p=0.011), with curriculum flexibility (β=0.100, p=0.013), internship participation (β=0.100, p=0.030), independent projects (β=0.110, p=0.011), and technological support (β=0.120, p=0.006) contributing meaningfully to learning outcomes. Notably, institutional support emerges as the strongest predictor (β=0.700, p<0.001) and significantly mediates the relationship between MBKM components and learning quality. Qualitative findings further reveal that the effectiveness of MBKM implementation depends on the alignment between institutional policies, operational support, and the integration of religious moderation values in learning practices. This study contributes to the literature by providing an integrated empirical model linking MBKM implementation, institutional support, and learning quality within value-oriented higher education systems. The findings underscore the importance of strengthening institutional readiness, ensuring equitable program implementation, and embedding inclusive Islamic values to enhance transformative learning in pluralistic societies.